Perbandingan Peforma Motor Koil Standar Dan Busi Standar Dengan Koil Racing Dan Busi Racing Menggunakan Bahan Bakar Pertamax 98 - Swastika Pascal Rafsanjanu; Namariq Masna; Ari Wicaksono; Panca Putra Hasugian; Trisma Jaya Saputra (Fakultas Teknik Universitas Cenderawasih, 2023)
A motorbike is one of the secondary needs of society, therefore the performance of the machine must also be considered, especially when choosing one of the components of the machine to be repaired or replaced. To get good motor performance, it must be balanced with a good ignition system too, so that the electricity supply is sufficient to do maximum work on the engine. The purpose of this study was to determine engine performance by comparing the ignition system between the use of standard coils and standard spark plugs with racing coils and racing spark plugs with Pertamax 98 fuel. The research was carried out using experimental methods or testing with the help of a dyno. From a comparative study of standard and racing ignition components on a Yamaha RX King 132cc motorbike, by replacing the spark plugs and coils that have been done, the results show that the highest power and torque values are obtained by replacing the racing coil and spark plugs. This is because the combustion in the cylinder chamber is better by replacing the racing ignition components.